Features of pregnancy and childbirth in women with congenital malformations of the fetus development - S. R. Halych; D. M. Schurko; M. I. Schurko (Kazimierz Wielki University, 2015)
Halych S. R., Schurko D. M., Schurko M. I. Features of pregnancy and childbirth in women with congenital malformations of the fetus development. Journal of Education, Health and Sport. 2015;5(3):62-67. ISSN 2391-8306. DOI: 10.5281/zenodo.16211 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A62-67 https://pbn.nauka.gov.pl/works/547309 http://dx.doi.org/10.5281/zenodo.16211 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   FEATURES OF PREGNANCY AND CHILDBIRTH IN WOMEN WITH CONGENITAL MALFORMATIONS OF THE FETUS DEVELOPMENT   S. R. Halych, D. M. Schurko, M. I. Schurko   Odessa National Medical University   Key words: pregnancy, childbirth, women, congenital malformations, fetus development.   Abstract   There is a very high percentage (39.8%) of  childbirth at the age of 30 years old and more. Pregnant patients with CMF are subjects to complications, including predominating placental dysfunction (46.7%), which manifested itself in the form of fetus's development retardation (26.3%), hypamnion (13.5%) or a combination of fetus's development retardation and hypamnion (6.9 %). Early preeclampsia (40%), threatened miscarriage (35%), hydramnios (19.03%), preeclampsia (25%), wrong position of the fetus and placenta (20%) are among other complications of pregnancy course. Parturient women who had fetal birth defects developed complications of childbirth, including a violation of the child's state (fetal distress - 31%), and abnormal contractions (anomalies of labor activity - 18%; premature rupture of the amniotic membranes - 18%). The high frequency of operative delivery by cesarean section (47%) needs further careful analysis of the indications.